People's Republic of China-Hong Kong Special Administrative Region Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper characterizes the rapid expansion of Hong Kong Special Administrative Region's (Hong Kong SAR) economic ties with the Mainland over the last two decades. It examines the possible impact on Hong Kong SAR of policy developments in the Mainland. The paper concludes that as integration has progressed, developments in various sectors of the Hong Kong SAR economy have become increasingly tied to developments on the Mainland. This paper also analyzes the initial episode of strong-side pressures on the Hong Kong dollar and, in particular, the Hong Kong Monetary Authority response.